Al-qudrah ʿalā taḥdīd al-fikrah al-raʾīsah wa-al-fikrah al-thanawiyyah fī al-nuṣūṣ al-Islāmiyyah ladā ṭullāb Qism Taʿlīm al-Lughah al-ʿArabiyyah fī al-Jāmiʿah al-Islāmiyyah Jakarta - Raswan, Raswan; Nurâ€™Aini, Tsamroh; Royani, Ahmad; Nawawi, Mukhshon; Abdul Wahab, Muhbib (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The objectives of the research are to reveal the ability of students of the Department of Arabic Language Teaching to identify the main and secondary idea of a basic problem faced by them to identify the main idea and the secondary idea. This research is qualitative research using the descriptive approach. The researcher takes the sample from 22 students in class "A" Department of Arabic Language Teaching. The data collection methods used by the researcher are interview, observation and written tests. After processing and analyzing the data, the researcher obtains that the average score of students in the Department of Arabic Language Teaching Syarif Hidayatullah Islamic University Jakarta to determine the main idea and the secondary idea is 48.36 with a grade of "fail" because the score falls between 0-45. From here we know that most of them are unable to identify the main idea and the secondary idea. The main problems that students face in determining the main idea and the secondary idea are the students' understanding of the content and their poor understanding of grammatical and morphological rules.